DESIGN AND BUILD OF CUTTING AND GUIDE UNITS RICE HARVESTING MACHINE WITH HARVEST SLIDER TYPE IN DARMARAJA DISTRICT, SUMEDANG REGENCY - Bambang Eko Saputro (JESA-Jurnal Edukasi Sebelas April, 2022)
Agricultural land with terraces and having an area per plot of less than 0.1 ha, is difficult to reach by large-sized and large-capacity agricultural machines. The Harvest Slider type rice harvester is an agricultural machine that can be used on small land and terraces. The purpose of this study was to design a cutter and guide unit for a rice harvesting machine that is easy to use on small land and terraces. The machine observation parameters measured were the effective field capacity, the effectiveness of the cutting unit, the effectiveness of the steering unit, fuel consumption and harvested rice loss. The work results show the effectiveness of the cutting unit is 99.56% and the steering unit is running well, which is indicated by the percentage of the effectiveness of the directing unit is 100%. The results of the performance test showed that the KLE for harvesting this machine was 0.05 ha/hour, fuel consumption was 1.2 l/hour, grain loss during harvesting was 2.1%. This shows that the Harvest Slider type rice harvester is on terraced and small land that cannot be reached by large harvesters.